The early life microbiota protects neonatal mice from pathological small intestinal epithelial cell shedding. Issue 5 (6th April 2020) - Hughes, Kevin R.; Schofield, Zoe; Dalby, Matthew J.; Caim, Shabhonam; Chalklen, Lisa; Bernuzzi, Federico; Alcon‐Giner, Cristina; Le Gall, Gwénaëlle; Watson, Alastair J. M.; Hall, Lindsay J.
Abstract: The early life gut microbiota plays a crucial role in regulating and maintaining the intestinal barrier, with disturbances in these communities linked to dysregulated renewal and replenishment of intestinal epithelial cells. Here we sought to determine pathological cell shedding outcomes throughout the postnatal developmental period, and which host and microbial factors mediate these responses. Surprisingly, neonatal mice (Day 14 and 21) were highly refractory to induction of cell shedding after intraperitoneal administration of liposaccharide (LPS), with Day 29 mice showing strong pathological responses, more similar to those observed in adult mice. These differential responses were not linked to defects in the cellular mechanisms and pathways known to regulate cell shedding responses. When we profiled microbiota and metabolites, we observed significant alterations. Neonatal mice had high relative abundances of Streptococcus, Escherichia, and Enterococcus and increased primary bile acids. In contrast, older mice were dominated by Candidatus Arthromitus, Alistipes, and Lachnoclostridium, and had increased concentrations of SCFAs and methyamines. Antibiotic treatment of neonates restored LPS‐induced small intestinal cell shedding, whereas adult fecal microbiota transplant alone had no effect. Our findings further support the importance of the early life window for microbiota‐epithelial interactions in the presence of inflammatory stimuli and highlights areas for further investigation.